Development of Ceria-Based Microtubular Solid Oxide Fuel Cells. (21st September 2015) - Sumi, Hirofumi; Yamaguchi, Toshiaki; Shimada, Hiroyuki; Hamamoto, Koichi; Suzuki, Toshio
Abstract : It is well known that gadolinia-doped ceria (GDC) has high oxide-ion conductivity for electrolyte, and it improves electrochemical activities for fuel oxidation and oxygen reduction for electrodes of solid oxide fuel cell (SOFC). In this work, we investigated the usage of ceria for cathode, anode and electrolyte of microtubular SOFCs for low temperature operation and direct hydrocarbon utilization.